Help with choosing the right disinfectants - Chooi, Wen Han; Long, Chiau Ming * (Star Media Group Berhad, 2021)
Malaysia's National Pharmaceutical Regulatory Agency (NPRA) and the United States' Environmental Protection Agency (EPA) recently issued new guidelines to assist consumers in choosing safe and effective disinfectant products to combat Covid-19